Issues without tears : a layman's manual of current issues. - Letisia R. Constantino (Quezon City : Karrell, 1984)
Annual accumulations of the materials issued by TAP of the education Forum . Editor: 1981-
Keywords: Philippines -- Societies, etc. -- Period; Teachers -- Philippines -- Period